Penyuluhan Fiqih Wanita Kepada Remaja Putri Dsn. Mulyorejo Ds. Kampung Baru Kec. Kepung Kab. Kediri - Kholifatur Rosyida (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2022)
Many girls do not have a proper understanding that menstruation (Menstruation) is a normal biological process. They actually only knew him at the time of menarche, aka the first time they experienced menstruation. The real Baligh for women begins when the first menstrual blood (Haid) comes out. The first menstruation is usually experienced by women starting at the age of nine years counted with the month of Qomariyah, but it can also be more. Menstruation is a woman's nature which indicates that the woman is healthy and her reproductive system is running well. This counseling activity is in the form of delivering material, asking questions and repeating the material presented as well as practices related to women's fiqh as well as the problems that occur in a woman including menstrual blood, postpartum and istihadloh as well as all worship related to women during their discharge period. blood (menstruation) The type of research used in this study is a type of PAR research or can be called Participatory Action Research. PAR (Participatory Action Research) research is a research model that involves all relevant parties to examine an ongoing action in order to make changes and improvements for the better. The thing that underlies this research is to get the desired change results. This type of research Participatory Action Research (PAR) has three benchmarks, namely participation, research and action. All research is related to each other, all three must be implemented in action. The three benchmarks work together to change or make improvements from the previous one. Participatory Action Research as a benchmark for research efforts carried out, so that there is change and is useful in the local community. According to research expert Hawort Hall, Participatory Action Research (PAR) is research that involves all elements of the researcher himself and those who pursue change must fully cooperate in all stages of the research..